Older adults' attitudes toward using Euthanasia at the end-of life: cancer vs. Parkinson's disease - Lifshitz, Rinat; Bachner, Yaacov G.; Carmel, Sara (Frontiers in Public Health, 2024)
Background: There is a paucity of studies that compare older adults' attitudes towards Euthanasia in two different terminal illnesses. Moreover, these studies did not relate to potentially influencing psycho-social factors. The current study aimed to examine the impact of a diverse range of variables on attitudes among older adults towards Euthanasia in two medical conditions: cancer and Parkinson's disease. Methods: A total of 501 individuals aged 75 and above participated in the study. Attitudes towards Euthanasia were measured using vignettes which described two conditions: an 80-year-old man with metastatic cancer and another man in an advanced stage of Parkinson's disease. The questionnaire included measures of relevant experience (with a close family member or a friend dying from a terminal illness), selfefficacy, will to live, satisfaction with life, will to prolong life, fear of death and dying, social support and psycho-social characteristics. The data were analyzed using hierarchical linear regression models. Results: A more positive attitude towards Euthanasia was found in the case of cancer compared to Parkinson's disease. Being a woman, having more years of education, lower level of religiosity, greater fear of death and dying and higher self-efficacy contributes to more favorable attitudes towards Euthanasia in both end-of life conditions. Conclusions: The finding that attitudes towards Euthanasia are statistically significantly more positive in the case of cancer compared to Parkinson's disease can be attributed to the greater prevalence of cancer in the population, and to the public's awareness of the suffering associated with each of these medical conditions. Beyond the important role of the socio-demographic characteristics of gender, education, and religiosity, it appears that fear of death and dying and self-efficacy are important psychological factors in explaining attitudes towards Euthanasia in both illnesses among older people. These findings shed light on older adults' attitudes towards Euthanasia in debilitating illnesses.